2018
DOI: 10.1016/j.ibror.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of local and remote cellular damage caused by spinal cord and peripheral nerve injury using a heat shock signaling reporter system

Abstract: HighlightsThe HSE-RFP reporter detects primarily- and secondarily-damaged neural cells in spinal cord injury.The HSE-RFP reporter detects primarily- and secondarily-damaged neural cells in sciatic nerve injury.Reporter-positive secondarily-injured neurons show altered physiological properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Our previous studies have shown that HSE drives reporter expression not only in the brain but also in many organs and tissues throughout the body of the embryo, including the eyes, heart, lung, and limb bud, in response to prenatal exposure to environmental insults [12]. Detection of cellular damage is also not limited to that of prenatal insults, but includes postnatal insults such as spinal cord or sciatic nerve injury [36]. Therefore, it is expected that these transgenic mice enable long-term tracing of neural as well as non-neural cell lineages affected by various types of chemical, infectious, or physical environmental factors during both prenatal and postnatal periods.…”
Section: Tracing the Lineage Of Cells Prenatally Affected By Environmmentioning
confidence: 99%
“…Our previous studies have shown that HSE drives reporter expression not only in the brain but also in many organs and tissues throughout the body of the embryo, including the eyes, heart, lung, and limb bud, in response to prenatal exposure to environmental insults [12]. Detection of cellular damage is also not limited to that of prenatal insults, but includes postnatal insults such as spinal cord or sciatic nerve injury [36]. Therefore, it is expected that these transgenic mice enable long-term tracing of neural as well as non-neural cell lineages affected by various types of chemical, infectious, or physical environmental factors during both prenatal and postnatal periods.…”
Section: Tracing the Lineage Of Cells Prenatally Affected By Environmmentioning
confidence: 99%
“…The neuropathological process following SCI is associated with cellular stresses by affecting activation of inflammation, reactive gliosis, and neuronal survival [ 33 ]. Though HSF1 has been shown to be dynamically regulated in the injured cord [ 34 ], its exact roles in the regulation of cell events have not been fully unveiled. Given that endogenous HSF1 is sufficient in inhibiting the expression of inflammatory cytokine TNF-α and IL-1β, the hallmarks of A1 astrocyte secretion [ 4 , 27 , 28 ], it is assumed that HSF1 may act to control reactive astrocyte states following SCI.…”
Section: Introductionmentioning
confidence: 99%